Interactions between the Ecological Dejiala River Properties, Southern Iraq - Abed, Intisar F.; Nashaat, Muhanned R. (Iraqi Journal of Science, 2018)
This study was the first of its kind on the Dejiala River, which is considered one of the main branches of the Tigris River in Wasit Province. Therefore, the study aimed to investigate of some physical and chemical properties of water in the Dejiala River. Monthly sampling stations were conducted for 12 months, which was starting from January to December 2016, during those five stations was chosen which divided along about 58 Km of river; each station was located at a distance of ±10 Km. The results of the study showed a clear correlation between air and water temperature in all stations. Turbidity was recorded a value ranging from 2.36-116 NTU. It was found that the water of the Dejiala was Oligohaline, weak alkaline and well ventilated due high concentrations of dissolved oxygen. The Dejialah River considered as questionable clean water according to BOD5 value. While the total alkalinity values were recorded from 30.5-427 mg/L, so these values were higher than the normal permissible limits for the Iraqi and international water standards, which is 20-200 mg /L CaCO3. It was also found that the water of the Dejiala River was very hard, as well as the it was within the permissible limits of natural water (200 mg/L Ca and 150 mg/L Mg). As for sulphate concentrations it has ranged from 40-150 mg/L, while bicarbonate was recorded values ranged from 120-180 mg/L. On the other hand, the TDS and TSS were recorded values ranged from 0.2-0.61 g/L and 1-171 mg/L, respectively. While nitrates recorded values from 0.787-2.505 mg/L which was below the normal permissible limits (15 mg/L) for the Iraqi water standards. Also, orthophosphates were recorded value from 0.011-0.082 mg/L.